Analisis Kualitas Perairan Pesisir Sanur, Bali terhadap Aktivitas Pariwisata dan Limbah Domestik - I Made Arya Wiguna; Ni Luh Putu Saraswati; I Gusti Ngurah Pratama (Journal of Marine Fisheries, 2025)
This study investigates the water quality of coastal waters in Sanur, Bali, with respect to tourism intensity and domestic wastewater discharge. The Sanur coastline is one of Bali’s major tourist destinations, experiencing high human activity and potential pollution inputs from hotels, restaurants, and residential areas. The objectives of this study were to evaluate key water quality parameters (BOD, nutrients, coliform, turbidity, and DO), to assess spatial and temporal variability, and to determine the relationship between tourism activity and domestic effluent. Water samples were collected from six coastal stations during both peak and off-peak tourism seasons and analyzed according to APHA standard methods. Results showed significant seasonal differences: during peak tourism periods, concentrations of nitrate, phosphate, and coliforms exceeded permissible thresholds, while dissolved oxygen levels decreased. Areas near hotel clusters and domestic drainage outlets showed the most degraded quality. The findings indicate that tourism and domestic wastewater significantly affect Sanur’s coastal water quality. This study emphasizes the urgent need for improved wastewater treatment infrastructure and sustainable tourism management policies to protect Bali’s coastal ecosystem integrity.